Aerosol trace metals, particle morphology and total gaseous mercury in the atmosphere of Oxford, UK - Witt, M; Meheran, N; Mather, T; de Hoog, J; Pyle, D (2010)
An investigation of atmospheric trace metals was conducted in Oxford, UK, a small city ∼60 miles northwest of London, in 2007 and 2008. Concentrations of Sr, Mo, Cd, Pb, V, Cr, Mn, Fe, Co, Ni, Cu and Zn in aerosol were measured in bulk and size segregated samples. In addition, total gaseous mercury (TGM) concentrations were monitored semi-continuously by cold vapour-atomic fluorescence spectroscopy. Metal concentrations in Oxford were intermediate between previously reported levels of UK rural and urban areas for most metals studied and levels of Cd, Ni and Pb were within European guidelines. Metal concentrations appeared to be influenced by higher traffic volume on a timescale of hours. The influence of traffic on the aerosols was also suggested by the observation of carbonaceous particles via scanning electron microscopy (SEM). Air mass back trajectories suggest air masses arriving in Oxford from London and mainland Europe contained the highest metal concentrations. Aerosol samples collected over Bonfire Weekend, a period of intense firework use and lighting of bonfires in the UK, showed metal concentrations 6-46 times higher than at other times. Strontium, a tracer of firework release, was present at higher concentrations and showed a change in its size distribution from the coarse to fine mode over Bonfire Weekend. The presence of an abundance of spherical Sr particles was also confirmed in SEM images. The average TGM concentration in Oxford was 3.17 ng m-3 (st. dev. 1.59) with values recorded between 1.32 and 23.2 ng m-3. This is a higher average value than reported from nearby rural locations, although during periods when air was arriving from the west, similar concentrations to these rural areas were seen in Oxford. Comparison to meteorological data suggests that TGM in Oxford's air is highest when wind is arriving from the east/southeast. This may be due to emissions from London/mainland Europe with a possible contribution from emissions from a local crematorium situated 4 miles east of the sampling site. A diurnal pattern was also observed in the TGM data with a minimum concentration during the day when mercury may have been diluted by thermal mixing of the atmospheric boundary layer. Additionally, this diurnal pattern may reflect variations in a local source of TGM. © 2010 Elsevier Ltd. All rights reserved.